Pyruvate Kinase M2 Mediates Glycolysis Contributes to Psoriasis by Promoting Keratinocyte Proliferation - Liu, Yun-zi; Xu, Ming-yuan; Dai, Xiao-yu; Yan, Lang; Li, Lei; Zhu, Rui-zhen; Ren, Li-jun; Zhang, Ji-qian-zhu; Zhang, Xiao-fang; Li, Jin-feng; Tian, Yi-jun; Shi, Wen-jing; et al. (Frontiers in Pharmacology, 2021)
Psoriasis is characterized by keratinocyte proliferation and immune cell infiltration. M2 isoform of pyruvate kinase (PKM2) was reported to have an important role in cell proliferation, which is a rate-limiting enzyme that regulates the final step of glycolysis. However, how PKM2 regulates cell metabolism and proliferation in psoriatic keratinocytes is still poorly understood. Interestingly, we found that PKM2 was highly expressed in psoriatic epidermis from patients and mouse models. PKM2 overexpression promoted keratinocyte glycolytic metabolism while knockdown inhibited keratinocyte proliferation and glycolysis. Mice lacking PKM2 specifically in keratinocytes, pharmacological inhibition of PKM2 or glycolysis inhibited keratinocyte proliferation and showed obvious remission in an imiquimod-induced psoriatic mouse model. Moreover, the inhibitor of the EGF-receptor blocked EGF-stimulated PKM2 expression and glycolysis in keratinocytes. We identify PKM2 as an upregulated gene in psoriasis. PKM2 is essential in keratinocyte over-proliferation and may represent a therapeutic target for psoriasis.